Genome-wide identification and salt stress-responsive expression profiling of Aux/IAA gene family in Asparagus officinalis - Shuangshuang Wen; Jiali Ying; Youju Ye; Yunfei Cai; Lebin Li; Renjuan Qian (BMC Plant Biology)
Abstract Background The Aux/IAA gene family encodes proteins that are central to auxin signaling and plant growth regulation. While Asparagus officinalis is a globally cultivated crop valued for its edible shoots, medicinal uses, and economic significance, the specific regulatory mechanisms and stress-responsive functions of Aux/IAA genes in this species remain largely uncharacterized. Previous studies have demonstrated Aux/IAA involvement in abiotic stress responses, but their roles in A. officinalis have not been systematically investigated. This study fills this gap by identifying candidate Aux/IAA genes in A. officinalis and characterizing their expression dynamics under salt stress, providing insights into their potential contributions to stress resilience. Results A comprehensive genome-wide analysis was conducted, revealing 17 Aux/IAA genes in A. officinalis. The results revealed that the AoIAA proteins featured a conserved Aux/IAA domain while demonstrating variability in their protein motif composition. Employing comparative genomics and evolutionary analyses, we classified the Aux/IAA genes into two major groups. Gene duplication analysis further identified two pairs of WGD/segmental duplication genes. The study of cis-regulatory elements in AoIAA gene promoters identified links to phytohormone signaling and abiotic stress responses. Additionally, the expression patterns of AoIAAs in A. officinalis differed among various tissues. The AoIAAs responded differently to salt treatment, notably with AoIAA1, AoIAA10, and AoIAA12 expression increasing alongside higher salt concentrations, highlighting their role in salt stress adaptation. Conclusion This study systematically characterized the Aux/IAA gene family in A. officinalis, highlighting their diversity and revealing structural and regulatory features. The findings provide a foundational resource for elucidating the biological functions and molecular mechanisms underlying Aux/IAA-mediated responses to salt stress and growth regulation in this species.